Role of think tanks in context of public policies in Poland: casus of energy policy - Czywilis, Dariusz; Niebylski, Michał (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The Polish energy policy is one of the crucial elements of country’s ratio legis. As a public policy, it is a common ground for multiple groups of interest and their activities aimed at achieving what they perceive as a success. It may be maintaining the structure of the Polish energy industry, modernizing it in accordance of the EU’s directives, reducing the energy prices or achieving independence from supplies brought in from one country, to achieve security through diversification. Think tanks in Poland are active participants in the conflict of interests presented by M. Considine: they act for achieving the change in the Polish energy policy and they aim at influencing the government and other political bodies to obtain legal regulations which reflect the think tank’s set of values. Their presence in the game of interest reflects the theoretical approach of Josef Braml, and shows the possibilities and limitations of subjects from the “third sector” in their interaction with administrative bodies. The major handicap of expert institutions is limited by the possibility of imposing political change through the systemic (legal) means. On the other hand, as it is indicated by example of Instytut Sobieskiego and Law and Justice (Prawo i Sprawiedliwość) party, they are capable of influencing the program through participation in the works of the “shadow cabinet” and persuading the party members to include the postulates of increased regulation and maintenance on hard coal as the primary energy source into political agenda, which increases substantial knowledge and preparation for debate on the MP’s side.